Launch of the National Agriculture Innovation and Technology Policy (NATIP) 2022-2027 (Nigeria) - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2022)
26 August 2022 marked an important day for the Nigerian agricultural sector as the Federal Ministry of Agriculture and Rural Development (FMARD) launched a new agriculture policy called the National Agricultural Technology and Innovation Policy (NATIP) in the nation’s Federal Capital Territory (FCT) to provide a roadmap for the transformation of the agri-food systems in Nigeria. NATIP has a 6-year (2022 – 2027) time frame to generate thrust, capabilities and massive public and private sector investments for successful implementation.